Implementation of character education discipline for students at the Nurul Ichsan Islamic Boarding School, Sumberejo Village, Gedangan District, Malang Regency - Nurzaharah; Adi Satmoko, Agus (Universitas Negeri Surabaya (Unesa), 2025)
An Character education is an important education in teaching and guiding students to apply character values in everyday life. Dicipline is a trait that students must have if they want to deal with social problems in the school environment an islamic boarding schools. The implementation of disciplinary character education will be more optimal if supported and through cooperation from various parties, so that disciplineis not only instilled in school activities or islamic boarding schools but also at home. The formulation of the problem in this tudy is how the process of islamic boarding school administrators impement disciplinary character education for students in the context of time discipline, obeyin gregulations, and discipline in worship at islamic boarding schools. Research at the Nurul Ichsan islamic boarding scholl on disciplinary character education aims to provide a clear and in-depth explanation of the develoment of disciplinary character in the Nurul Ichsan islamic boarding scholl. The type of research used is descriptive field research. The data collection methods used are interview mwthods, observation, and documentation in the field. The result of this study indicate that the implementation of disciplinary character education for students at the Nurul Ichsan islamic boarding school is carried out very well by the rules and regulations of the islamic boarding school. Meanwhile, in the internalizition of character education, discipline use the alilm method or teaching method, mas ulyatun’ilm or advice, uswatun hasanah or role model. Al’itimadhu’ala nafsi or habituation, amar ma’ruf nahi munkar, and warnings which are integrated into activities in islamic boarding schools.